The Impact Of Limited Facilities And Infrastructure On Midwives' Performance In Midwifery Care In The Elelim Public Health Center, Elelim District, Yalimo Regency, Papua Mountain Province - Jean Christy Ade Putri; Tenny Tarnoto; Cakrawati R Cakrawati R (International Journal of Health Sciences, 2026)
ABSTRACT The availability of health facilities and infrastructure is a crucial factor supporting the success of midwifery services. In remote areas such as Elelim District , Yalimo Regency , Papua Mountains, limited health facilities remain a challenge in the implementation of midwifery care. This situation has the potential to impact midwives' performance in providing optimal services to the community. This study aims to analyze the impact of limited facilities and infrastructure on midwives' performance in implementing midwifery care at the Elelim Community Health Center . The study used a quantitative approach with a descriptive analytical design using a cross-sectional method . The study sample consisted of 35 midwives working at the Elelim Community Health Center and the health service network in the Elelim District area . Data were collected using questionnaires and observation sheets. Data analysis was performed using the Chi- Square test . The results showed that 68.6% of respondents assessed that facilities and infrastructure were still limited, while 62.9% of midwives' performance was considered adequate. The analysis revealed a significant relationship between the availability of facilities and infrastructure and midwife performance (p = 0.001).